Tracing the tidal streams of the Sagittarius dSph, and halo Milky Way features, with carbon-rich long-period variables - Huxor, Avon P.; Grebel, Eva K. (Monthly notices of the Royal Astronomical Society, 2015)
Abstract. We assemble 121 spectroscopically confirmed halo carbon stars, drawn from the literature, exhibiting measurable variability in the Catalina Surveys.
Gesehen am 03.06.2020